2017
DOI: 10.1007/s00431-017-3003-z
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ education vs rhinopharyngeal clearance in children with upper respiratory infections: impact on children’s health outcomes

Abstract: This study showed that the most positive impact on children's health outcomes occurred when combining health education of caregivers, regarding children's respiratory infections, with a rhinopharyngeal clearance protocol in children with URTI. What is Known: • Upper Respiratory Tract Infections are very common in children but still do not have an effective pharmacological treatment. • This generates a great burden of disease for the child and families, increasing the use of antibiotics. What is New: • This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…For this update, we screened 2486 citations published since the original search (June 2016) and included 13 additional studies (8 RCTs, 5 observational studies) in 14 publications. 16 – 29 The study characteristics and quality assessment for studies included in the CER can be found in the AHRQ report, 11 and studies added in this update can be found in Table 1 . Cumulatively, there were 95 (86%) mostly fair-quality studies: 65 RCTs and 30 observational studies ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…For this update, we screened 2486 citations published since the original search (June 2016) and included 13 additional studies (8 RCTs, 5 observational studies) in 14 publications. 16 – 29 The study characteristics and quality assessment for studies included in the CER can be found in the AHRQ report, 11 and studies added in this update can be found in Table 1 . Cumulatively, there were 95 (86%) mostly fair-quality studies: 65 RCTs and 30 observational studies ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Viral infections are predominant, but bacterial super-infections may frequently appear. Consequently, there is an overuse/misuse of antibiotics by primary care doctors that in turn induces antibiotic resistance [34,35]. Moreover, biofilm causes frequent antibiotic unsuccess and 25-45% of children with severe RRI need surgical intervention [36,37].…”
Section: Recurrent Respiratory Infectionsmentioning
confidence: 99%
“…8 Also, regarding RRC, there is some evidence of its effect in clearing the upper respiratory tract, and very encouraging results given that it is a non-pharmacological form of intervention without clinically relevant side-effects. 23 , 28 …”
Section: Discussionmentioning
confidence: 99%
“… 10 , 20 RRC was accomplished by instillation of isotonic saline solution (0.9% NaCl) through the nostrils, followed by mouth closure, forcing inspiration through the nasals cavities and removing secretions from this area to the oropharyngeal cavity. 21 , 22 , 23 These maneuvers were carried out during consecutive breathing cycles in order to promote the mobilization of secretions towards the proximal airways. This stimulated the mechanical receptors and made the children cough spontaneously.…”
Section: Methodsmentioning
confidence: 99%